„Przestępstwa terrorystyczne” i przestępstwa o charakterze terrorystycznym w obowiązującym kodeksie karnym – niedoskonała ochrona bezpieczeństwa państwa i jego obywateli - Michalska-Warias, Aneta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The paper emphasises the state’s obligation to provide safety, also from terrorist threats. The dogmatic analysis of the binding anti-terrorist solutions of the Polish Criminal Code is presented from this point of view. The paper discusses the mutual relationship between an offence of a terrorist character, as defined in Art. 115 § 20 of the Criminal Code and the types of offences present in the Criminal Code which refer specifically to the phenomenon of terrorism, which are labelled by the Author as “terrorist offences”. It is stressed that the definition from Art. 115 § 20 of the Criminal Code is of a strictly juridical character, therefore all offences meeting the statutory criteria should be considered of terrorist character, even if they have no connection with the phenomenon of terrorism in its criminological sense. On the other hand the “terrorist offences” described in the Criminal Code (as e.g. terrorist training or financing of terrorism) cannot, intrinsically, be considered offences of a terrorist character in the meaning of the legal definition. Therefore some modifications of Art. 65 § 2 of the Criminal Code have been proposed so as make it possible to treat the perpetrators of such terrorist offences in the same way as the perpetrators of offences of a terrorist character during the application of the probation measures and at the stage of punishment execution. Thus, it is claimed, the safety of citizens (which is a constitutional value), would be further enhanced.